2023
DOI: 10.3390/pharmaceutics15112530
|View full text |Cite
|
Sign up to set email alerts
|

Design, Development, Evaluation, and In Vivo Performance of Buccal Films Embedded with Paliperidone-Loaded Nanostructured Lipid Carriers

Fahad Mohammed AlMulhim,
Anroop B. Nair,
Bandar Aldhubiab
et al.

Abstract: The therapeutic effectiveness of paliperidone in the treatment of schizophrenia has been limited by its poor oral bioavailability; hence, an alternative route could be appropriate. This study investigates the feasibility of developing a buccal film impregnated with paliperidone-loaded nanostructured lipid carriers (NLCs) and assesses the potential to enhance its bioavailability. Box–Behnken-based design optimization of NLCs was performed by examining the particles’ physical characteristics. The polymeric film … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
(99 reference statements)
0
0
0
Order By: Relevance
“…Therefore, encapsulating nanoparticles within films can improve the performance or modify the properties of both the drug and the film, leading to enhanced functionality. AlMulhim et al [ 23 ] examined the possibility of creating a buccal film containing paliperidone-loaded nanostructured lipid carriers. They found that the pharmacokinetic profile in rabbits indicates the potential of buccal therapy, as demonstrated by a significantly higher AUC 0–12 and greater relative bioavailability than the control.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, encapsulating nanoparticles within films can improve the performance or modify the properties of both the drug and the film, leading to enhanced functionality. AlMulhim et al [ 23 ] examined the possibility of creating a buccal film containing paliperidone-loaded nanostructured lipid carriers. They found that the pharmacokinetic profile in rabbits indicates the potential of buccal therapy, as demonstrated by a significantly higher AUC 0–12 and greater relative bioavailability than the control.…”
Section: Introductionmentioning
confidence: 99%